Exploring a Flipped Learning Approach in Teaching Grammar for ESL Students - Chelster Sherralyn Jeoffrey Pudin (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2017)
In light of the recent implementation of MOOC, the world of academia has been abuzz about incorporating flipped learning as part of blended learning in the classroom. Educators have been experimenting and exploring with it using different approaches. Flipped learning is basically a pedagogical model which reverses classroom activities. Materials or contents are provided online (in learning management system or other learning platforms) and students will study the material prior coming to class. Therefore, classroom time can be used to engage in activities such as problem solving, discussion and analysis. This study set out to explore the effects of flipped learning approach in a grammar classroom through students’ perceptions on its effectiveness and feasibility. A total of 120 students with higher Malaysian University Entrance Test (MUET) were asked to complete a questionnaire which is then analysed through SPSS version 24. The analysis of the findings showed that most of the students were keen to learn grammar through flipped classroom as opposed to traditional grammar classroom. The findings of this study give ESL practitioners a better insight into students’ preference in learning grammar and ways to create better teaching through blended learning.